Vidian Nerve Neurofibroma Removed via a Transpterygoid Approach - McLaughlin, N.; Bresson, D.; Ditzel Filho, L.F. S.; Carrau, R. L.; Kelly, D. F.; Prevedello, D. M.; Kassam, A. B. (min - Minimally Invasive Neurosurgery, 2011)
Lesions originating in the vidian canal are extremely rare. Most frequently, they are extensions from contiguous carcinomas. We present a rare case of a vidian nerve neurofibroma and discuss its surgical management.A 62-year-old woman with a history of a basal cell skin cancer was evaluated for bilateral tinnitus. Imaging revealed a left-sided lesion at the medial aspect of the pterygoid process base, over the vidian canal. Under image-guidance, an endonasal endoscopic transpterygoid approach was performed. The histopathological examination supported the diagnosis of neurofibroma.Benign nerve sheath tumors of the vidian nerve should be considered in the differential diagnosis of a vidian canal lesion. Given the propensity of more aggressive tumors, a tissue diagnosis should be warranted in order to coordinate appropriate subsequent treatment. The expanded endonasal transpterygoid approach offers a safe, less invasive, and effective route to perform the excisional biopsy of such a lesion.
Keywords: vidian nerve; vidian canal; neurofibroma; endoscopy; expanded endonasal approach; transpterygoid approach